Evaluasi Kepuasan Masyarakat Terhadap Pelayanan Air Bersih PAMSIMAS Di Desa Tihu Kecamatan Bone Pantai - Nessa Fadila Modundo; Aryati Alitu; Arfan Usman Sumaga (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This research was conducted to assess the level of community satisfaction with clean water services provided through the PAMSIMAS (Community-Based Drinking Water and Sanitation Provision) program in Tihu Village, Bonepantai Subdistrict. Clean water is a fundamental necessity for life; however, the PAMSIMAS service still faces several issues, such as low water clarity and unstable supply, particularly during the rainy season. This evaluation aimed to identify the extent to which the community feels satisfied and to provide recommendations for program management improvement. This research employed a quantitative method with a descriptive design. The sample consisted of 60 respondents out of 150 active users, determined using the Slovin formula. Data were collected using a Likert-scale-based questionnaire covering seven main variables: water quality, continuity, reliability, accessibility, cost affordability, community participation, and responsiveness to complaints. The data were analyzed using SPSS with validity tests, reliability tests, and descriptive analysis. The results indicated that the majority of the community was reasonably satisfied with the PAMSIMAS clean water service, although complaints remained regarding water quality and availability. Then, validity and reliability tests confirmed that the research instruments were appropriate for use. The highest satisfaction levels were found in accessibility and affordability, while water quality and continuity received the lowest satisfaction scores. Overall, the PAMSIMAS clean water service in Tihu Village has provided considerable benefits; however, improvements are needed, particularly in technical aspects and water distribution management, to ensure sustainable and equitable service in the future.